Profesi Pendidik: Tantangan Dan Harapan - Nasrun Nasrun (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2017)
Abstract: Today’s educational issues include two things, namely: (1) educational practice is conducted without education science; and (2) the occurrence of several “mistake” of education. The problem is of course influenced by several factors that are very complex, among others, there are five main things that cause two things can happen, namely: (1) educators are not trained in advance to carry out tasks (untrained); (2) not well trained (undertrained); (3) are less concerned about their duties and obligations (uncommitted); (4) lower education facilities (under-facilitated); and (5) educators are underpaid so as to give rise to pragmatic educational attitudes and burden objections. The provision that educators are professionals carries the consequence that educators are required to meet their professional requirements. Education Institution of Education Personnel (LPTK) as an institution producing educators and educational staff very concerned conceptually-praxis as the center of orientation and guidance for the development and enforcement trilogy educator profession, namely: (1) basic educational scholarship; (2) the substance of the educator profession; and (3) the practice of educator profession to be mastered by educator candidates. Along with the development of the dynamics and challenges of education increasingly complex. Policies and regulations that continue to be simulated and implemented are now directed to deal with various dynamics developments and challenges. The efforts of professionalization of educators through various programs are also continuously conducted. The efforts being undertaken and carried out at this time of hope in the future leads to the birth of educator figures in which awaken the professional dignity based on: (1) useful service; (2) a commensurate exercise; and (3) get a healthy recognition from the government and the community.Abstrak: Permasalahan pendidikan dewasa ini mencakup dua hal, yaitu: (1) praktik pendidikan dilakukan tanpa didasari ilmu pendidikan; dan (2) terjadinya beberapa kecelakaan pendidikan. Permasalahan tersebut tentunya dipengaruhi oleh beberapa faktor yang sangat kompleks, antara lain ada lima hal pokok yang menyebabkan dua hal tersebut bisa terjadi, yaitu: (1) pendidik tidak dilatih terlebih dahulu untuk melaksanakan tugas-tugasnya (untrained); (2) tidak terlatih dengan baik (undertrained); (3) kurang peduli atas tugas dan kewajibannya (uncommitted); (4) fasilitas pendidikan rendah (under-facilitated); dan (5) pendidik dibayar rendah (underpaid) sehingga menimbulkan sikap pendidik yang pragmatis dan keberatan beban. Ketetapan bahwa pendidik adalah tenaga profesional membawa konsekuensi bahwa pendidik wajib memenuhi persyaratan profesionalnya. Lembaga Pendidikan Tenaga Kependidikan (LPTK) sebagai institusi penghasil pendidik dan tenaga kependidikan sangat berkepentingan secara konseptual-praksis sebagai pusat orientasi dan penuntun bagi pengembangan serta ditegakkannya trilogi profesi pendidik, yaitu: (1) dasar keilmuan pendidikan; (2) subtansi profesi pendidik; dan (3) praktik profesi pendidik yang harus dikuasi oleh calon pendidik. Seiring dengan perkembangan zaman dinamika dan tantangan dunia pendidikan semakin kompleks. Kebijakan dan regulasi yang terus digodok dan diimplementasikan saat ini diarahkan untuk menghadapi berbagai perkembangan dinamika dan tantangan yang terjadi. Upaya profesionalisasi pendidik melalui berbagai program juga terus dilakukan. Upaya-upaya yang sedang dilakukan dan dijalankan saat ini harapannya ke depan bermuara kepada lahirnya sosok-sosok pendidik yang di dalam dirinya terbangun kemartabatan profesi yang didasarkan atas: (1) pelayanan yang bermanfaat; (2) pelaksanaan yang bermandat; dan (3) mendapatkan pengakuan yang sehat dari pemerintah dan masyarakat.